2018
DOI: 10.3390/ma11122401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Preheating Temperatures on the Microstructure, Properties, and Residual Stress of 12CrNi2 Prepared by Laser Cladding Deposition Technique

Abstract: The 12CrNi2 alloy steel powder studied in the present paper is mainly used to manufacture camshafts for nuclear power emergency diesel engines. Laser cladding deposition is of great significance for the manufacture of nuclear power emergency diesel camshafts, which has the advantages of reducing material cost and shortening the manufacturing cycle. However, due to the extremely uneven heating of the components during the deposition process, a complex residual stress field occurs, resulting in crack defects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Therefore, determining how to reduce the deformation of thin-walled parts during laser cladding repair has become the focus of a body of research. The formation reason and action rules of stress and deformation in laser cladding are very complex, and many experts and scholars have conducted many related investigations on this topic [16][17][18][19][20][21][22]. Wang et al [23] used different types of lasers to study the properties of formed AISI316L stainless steel thin-walled parts, and found that the ultimate tensile strength of the sample produced by a pulse laser was higher than that of the sample produced by a continuous-wave laser.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, determining how to reduce the deformation of thin-walled parts during laser cladding repair has become the focus of a body of research. The formation reason and action rules of stress and deformation in laser cladding are very complex, and many experts and scholars have conducted many related investigations on this topic [16][17][18][19][20][21][22]. Wang et al [23] used different types of lasers to study the properties of formed AISI316L stainless steel thin-walled parts, and found that the ultimate tensile strength of the sample produced by a pulse laser was higher than that of the sample produced by a continuous-wave laser.…”
Section: Introductionmentioning
confidence: 99%
“…108 On the other hand, there were variations with sharp changes in the microhardness values of AlTiCrFeCoNi HEA at stage one of the experiments, which could be attributed to the small hardening effect in the heat-affected zones and the inner microstructure undergoing intricate phenomena before preheating under reoccurring thermal cycling resulting in the fluctuation in hardness values. 109 Consequently, the AlTiCrFeCoNi alloy's had higher hardness values at the first stage of experiments from 600 W to 1000 W attributed to the AlNi 3 phase and the BCC structure. 110 Nonetheless, there was a decline at the second stage of experiments from 1200 W to 1600 W with an average hardness ranging from 811 to 387 HV compared to AlCoCrFeNiCu HEA, which ranged from 389 to 837 HV after stage one and two of the experiments.…”
Section: Effect Of Laser Parameters On Hardnessmentioning
confidence: 94%
“…Laser has been widely utilized in automatic welding for automotive, electronics, and aircrafts [28]. Laser welding is an attractive option because laser is stable and repeatable.…”
Section: Methodsmentioning
confidence: 99%